THE PATTERN OF INFLUENCE OF THE ELECTROCHEMICAL FIXING LOESS SOILS’’ PARAMETERS ON THE CARRYING CAPACITY OF THE ANCHORS - Zocenko, M. L.; Trocenko, D. O.; Titarenko, V. A. (Science and Transport Progress, 2010)
The results of complex experimental investigations of influence of the electrochemical stabilization of loessial soils on the bearing capacity of anchors are presented.